Tax structure and economic growth in Malaysia/ Nurdiana Yasmin Jamaluddin - Jamaluddin, Nurdiana Yasmin (2018)
Economic growth in Malaysia is now keep increasing year by year. Previous literatures explaining the financial development and tax structure as the main factor of the economic growth. However, there is less discussion on the tax structures and the relationship between tax structures and economic growth is still inconclusive. Therefore, this research is to find out more on the extension on the relationship between tax structure and growth of economy in Malaysia. The growth of the economy is being measured by the proxy of Gross Domestic Product (GDP) as the dependent variable. The tax structures was determined by the property taxes, corporate income taxes, personal income taxes, consumption taxes, taxes on export, custom duties taxes and tax on goods and services. The country that used in this research is Malaysia. The data collected from annual data and the time period used from year 1990 to year 2015 (26 years).